1997
DOI: 10.1046/j.1365-2249.1997.4541471.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of low molecular weight heparin on mediator release by mast cells: preferential inhibition of cytokine production and mast cell-dependent cutaneous inflammation

Abstract: SUMMARYThere has been substantial evidence that suggests that heparin may modulate various aspects of immune function and inflammation in addition to its well known anticoagulant activity. In this regard heparin was found to suppress cell-mediated immune responses or asthmatic reactions to allergen challenge. In the present study we analyse the effects of low molecular weight heparin (LMWH) on mast cell degranulation and cytokine production in vitro and on the elicitation of IgE-mediated mast celldependent lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 34 publications
(67 reference statements)
0
44
1
1
Order By: Relevance
“…[27][28][29][30][31][32] Although the mechanisms behind the anticancer activity of LMWH remain poorly understood, these could involve an effect on the host immune response. [33][34][35][36][37][38] However, this hypothesis was not confirmed by the results of the current study, in which none of the measured cytokines was found to correlate with the beneficial survival effects of nadroparin. 28 Although a change in these cytokine concentrations would have given an indication of the general immune system activity against the tumor, the lack of such an effect cannot exclude a possible influence of LMWH on other immune markers or on immune pathways not reflected in circulating markers.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…[27][28][29][30][31][32] Although the mechanisms behind the anticancer activity of LMWH remain poorly understood, these could involve an effect on the host immune response. [33][34][35][36][37][38] However, this hypothesis was not confirmed by the results of the current study, in which none of the measured cytokines was found to correlate with the beneficial survival effects of nadroparin. 28 Although a change in these cytokine concentrations would have given an indication of the general immune system activity against the tumor, the lack of such an effect cannot exclude a possible influence of LMWH on other immune markers or on immune pathways not reflected in circulating markers.…”
Section: Discussioncontrasting
confidence: 65%
“…[27][28][29][30][31][32] The beneficial effects of LMWH on survival could be related to an effect on the host immune response, although data are limited, with discordant results published across the studies, possibly due to differences in experimental conditions. [33][34][35][36][37][38] Another possible mechanism with which to explain the anticancer activity of LMWH could be that LMWH interferes with the cross-talk between platelets and tumor cells. Platelets have the potential to promote several steps of the tumor progression and markers of platelet activation have been correlated with a worse prognosis in patients with cancer.…”
mentioning
confidence: 99%
“…Heparin acts as a potent competitive inhibitor of inositol 1,4,5-triphosphate-dependent calcium release from the endoplasmic reticulum (Ghosh et al, 1988), an effect that is considered to underlie the inhibition of human mast cells that has been described in vitro (Inase et al, 1993) and found to be independent of anticoagulant activity (Ahmed et al, 1997). LMWH has also been demonstrated to inhibit the release of cytokines from mast cells (Baram et al, 1997), and oligosaccharides derived from heparin have been found to inhibit the release of IL-4 and IL-5 from blood T lymphocytes (Ji et al, 2004). Heparin also inhibits the cytotoxic effects of tumor necrosis factor-a-activated eosinophils on endothelial cells (Slungaard et al, 1990), as well as the homotypic aggregation and chemotaxis of eosinophils in response to complement factor C5a, which is bound by heparin (Matzner et al, 1984;Teixeira et al, 1996).…”
Section: A Effects Of Heparin On Inflammation and Inflammatory Mediamentioning
confidence: 99%
“…LMWH preferentially inhibits tumor necrosis factor-α and interleukin 4 (IL-4) production. In vivo, subcutaneous injections of LMWH inhibit leukocyte infiltration associated with a late cutaneous response 9 . Use of LMWH, but not unfractionated heparin, leads to a dose-dependent increase in IL-6 from nonstimulated peripheral blood mononuclear cells isolated from healthy donors 10 .…”
Section: To the Editormentioning
confidence: 99%